2013
DOI: 10.1542/peds.2012-1892
|View full text |Cite
|
Sign up to set email alerts
|

Chest Compression Quality Over Time in Pediatric Resuscitations

Abstract: CC quality deteriorates similarly in child and adult manikin models. Peak work per compression cycle is comparable in both. Peak power output is analogous to that generated during intense exercise such as running. CC providers should switch every 2 minutes as recommended by current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 29 publications
(28 reference statements)
2
41
1
4
Order By: Relevance
“…Therefore, current pediatric resuscitation guidelines suggest that professionals should be switched every 2 min while performing CC. 16 Badaki-Makun et al 11 reported similar rates of fatigue in adult and child CPR, with a decrease in CC depth after 42 min of CPR. In comparison, two studies examined the rate of fatigue within 2 min of CPR in pediatric and neonatal healthcare professionals and reported no significant decay in CC, which is comparable to our results.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Therefore, current pediatric resuscitation guidelines suggest that professionals should be switched every 2 min while performing CC. 16 Badaki-Makun et al 11 reported similar rates of fatigue in adult and child CPR, with a decrease in CC depth after 42 min of CPR. In comparison, two studies examined the rate of fatigue within 2 min of CPR in pediatric and neonatal healthcare professionals and reported no significant decay in CC, which is comparable to our results.…”
Section: Discussionmentioning
confidence: 94%
“…14,15 Peak power output generated during pediatric resuscitation is comparable to power generated during intense exercise (for example, running 9 km h − 1 ). 11 In addition, peak work per compression cycle and deterioration of CC quality is comparable between adult and pediatric resuscitation. 11 The depth of CC can be translated into compression force, which is related to changes in intrathoracic pressure.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations